Indoor environmental quality and occupant satisfaction in green-certified buildings - Altomonte, Sergio; Schiavon, Stefano; Kent, Michael G.; Brager, Gail (Taylor & Francis, 2017)
Green building certification systems aim at improving the design and operation of buildings. However, few detailed studies have investigated whether green rating leads to higher occupant satisfaction with indoor environmental quality (IEQ). This research builds on previous work to address this. Based on the analysis of a subset of the Center for the Built Environment Occupant Indoor Environmental Quality survey database featuring 11,243 responses from 93 LEED-rated office buildings, we explored the relationships between the points earned in the IEQ category and the satisfaction expressed by occupants with the qualities of their indoor environment. We found that the achievement of a specific IEQ credit did not substantively increase satisfaction with the corresponding IEQ factor, while the rating level, and the product and version under which certification had been awarded, did not affect workplace satisfaction. There could be several reasons for this lack of relationships, some of which are outside the control of designers and beyond the scope of rating systems based primarily on design intent. We conclude with a discussion of the challenges and priorities that building professionals, researchers, and green building certification systems need to consider for moving us towards more comfortable, higher performing, and healthier green-rated buildings.